Enhancing Early Reading Skills Through Multisensory Contextual Learning: A Classroom Action Research Study with First-Grade Students with Learning Difficulties - Wulandari, Retno; Pujaningsih, Pujaningsih (Journal of Innovation and Research in Primary Education, 2025)
Early reading skills represent fundamental prerequisites for academic success, yet many first-grade students, particularly those with learning difficulties, struggle to master these competencies. This study investigated the effectiveness of multisensory contextual learning strategies in improving early reading skills among students with learning difficulties in inclusive classroom settings. A classroom action research design following Kemmis and McTaggart's spiral model was employed over three months (April-June 2025) at an inclusive elementary school in East Kalimantan, Indonesia. Twenty-five first-grade students participated, including four students with learning difficulties who served as the primary focus. The intervention utilized Visual, Auditory, Kinesthetic, and Tactile (VAKT) approaches integrated with contextual learning principles. Data collection employed observations, parent interviews, and cognitive assessments across two intervention cycles. Statistical analysis included paired-sample t-tests to evaluate pre-post intervention differences. Students with learning difficulties demonstrated statistically significant improvements across all measured domains. Cognitive scores increased from 15.62 to 21.25 (t = 6.45, p < 0.05), while affective domain measures improved from 1.42 to 2.42 (t = 6.16, p < 0.05). Pre-reading skills enhanced from 1.75 to 2.75 (t = 6.12, p < 0.05). Over 80% of participants achieved predetermined early reading indicators. Qualitative observations revealed increased confidence, motivation, and active participation in reading activities. The multisensory contextual approach effectively addressed reading difficulties by engaging multiple sensory pathways and connecting learning to students' experiential contexts. Findings support existing literature on neuroeducational benefits of multisensory instruction and validate contextual learning theories. The intervention's success using readily available materials demonstrates practical feasibility for diverse educational settings, contributing evidence for inclusive pedagogy and differentiated instruction approaches.